Zal. Sv. Ḟeodora po opisi Gidrograficheskoĭ Ėkspedit︠s︡īi Vostochnago okeana 1916 g. / Snimalʺ i chertili Kapitanʺ mal. pl. P. Silsonʺ - Russia. Glavnoe gidrograficheskoe upravlenīe (Vladivostok : Morskoe ministerstvo, Glavnoe gidrograficheskoe upravlenīe; Владивосток : Морское министерство, Главное гидрографическое управленіе, 1916)
Relief shown by form lines and spot heights. Depth shown by soundings and isolines.; Title translation: Gulf of Saint Theodore, according to the survey of the Hydrographic Expedition of the Eastern Ocean in 1916.; Greenwich meridian.; "Masshtabʺ 1/16800 ili 200 sazh. vʺ di︠u︡ĭmi︠e︡" = Scale 1/16800 or 200 fathoms in 1 inch.; "345" -- handwritten bottom right margin Grayscale; 1:16,800